The Bill of Rights - Stein, R. Conrad (Chicago Childrens Press, 1992)
Discusses the first ten amendments to the Constitution and the rights which they are intended to protect
American Corner
Includes index
11
Keywords: United States; United States -- Juvenile literature; Civil rights